The Berenstain Bears : Brother. Sister. Adventures! English language arts. - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012.; Berenstain, Mike, 1951-; Findaway World, LLC. (Solon, Ohio : Findaway World, LLC, 2016)
"It's time for more adventures with Brother and Sister Bear! Bear Country comes to life in these engaging and interactive digital book apps that will excite young readers, teach literacy fundamentals and boost reading confidence. Encourage literacy skills; Follow along with three fun ways to read; Learn new vocabulary with tappable text; Tap objects to hear their name read aloud"--
Berenstain Bears and the Big Spelling Bee --
Title from label.
Release date supplied by publisher.
Issued on Playaway Launchpad, a pre-loaded learning tablet.
Content and/or functionality of apps on this tablet may have been modified for use on this device.
Powered by rechargeable battery ; container includes one power charging cord with both USB and AC adapters.
Earphones not required for audio playback.
Keywords: Berenstain Bears (Fictitious characters) -- Interactive multimedia; Reading -- Interactive multimedia -- Study and teaching (Primary); Reading comprehension -- Interactive multimedia -- Study and teaching (Primary); Literacy -- Interactive multimedia -- Study and teaching (Primary); Vocabulary -- Interactive multimedia -- Study and teaching (Primary); Educational games; Video games; Mobile apps